2020
DOI: 10.1016/j.resuscitation.2020.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based crisis standards of care for out-of-hospital cardiac arrests in a pandemic

Abstract: Background & purpose Pandemics such as COVID-19 can lead to severe shortages in healthcare resources, requiring the development of evidence-based Crisis Standard of Care (CSC) protocols. A protocol that limits the resuscitation of out-of-hospital cardiac arrests (OHCA) to events that are more likely to result in a positive outcome can lower hospital burdens and reduce emergency medical services resources and infection risk, although it would come at the cost of lives lost that could otherwise be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“… Treatment 77 Natalzia et. al 89 Evidence-based crisis standards of care for out-of-hospital cardiac arrests in a pandemic Cohort Cardiac arrest events in the CARES database US ● Favorable outcomes were associated with initial shockable rhythms or arrest witnessed by EMS. ● A proposed crisis standard of care protocol suggested to only initiate out-of-hospital resuscitation in these patients resulted in a prevalence of 70.5% favorable neurological outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Treatment 77 Natalzia et. al 89 Evidence-based crisis standards of care for out-of-hospital cardiac arrests in a pandemic Cohort Cardiac arrest events in the CARES database US ● Favorable outcomes were associated with initial shockable rhythms or arrest witnessed by EMS. ● A proposed crisis standard of care protocol suggested to only initiate out-of-hospital resuscitation in these patients resulted in a prevalence of 70.5% favorable neurological outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…They state that this protocol could account for 70.5% of favorable neurological outcomes and provide 6.3 additional available hospital beds per patient. 89 …”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in the Korea by Jung et al (20), it was reported that 34.4% of the patients needed Advanced Cardiac Life Support (ACLS). Moreover, Natalzia et al (21) reported that 63.7% of the patients with COVID-19 suffered from an unstable situation. In this regard, our ndings indicate that the patient's condition may be worsen and require emergency intervention due to the nature of the disease (22), failure to refer to the health center on time due to fear of infection with the disease and intention to follow the home care (8).…”
Section: Resultsmentioning
confidence: 99%
“…Natalzia et al proposes a protocol to maximize cardiac arrest resources in EMS in which one should only initiate resuscitation of a patient in cardiac arrest if the arrest is witnessed or a shockable rhythm is present. They state that this protocol could account for 70.5% of favorable neurological outcomes and provide 6.3 additional available hospital beds per patient (89) .…”
Section: Discussionmentioning
confidence: 99%